MANFAAT HASIL BELAJAR MANAJEMEN USAHA BUSANA SEBAGAI KESIAPAN MENJADI FASHION BUYER DI CHAIN STORES - Rahmi Annissa; Katiah Katiah (Universitas Pendidikan Indonesia, 2015)
The progress of time resulted that an industrial players of fashion business is increasing, fashion buyer became one of the professions that take an important role in the field of fashion business. The purpose of this study was to obtain data on the advantages of fashion business management learning outcomes as a readiness to become a fashion buyer in chain stores, in terms of competence business management concept, fashion business opportunities, fashion business production management, marketing management and human resource management. The used research method is descriptive method. The technique of collecting data using questionnaires. The population in this study which are students of Prodi Pendidikan Tata Busana class of 2009 which is numbered 48 people. The research sample using random sampling by means of raffle population in determining that sample, so that the total sample was 30 people. The results showed most of students feel the benefits of learning outcomes in the fashion business management into a fashion buyer readiness in chain stores in terms of fashion business opportunities, fashion business production management, marketing management and human resource management. The results of this study can be used as information to develop and improve insight into the fashion business management so that students are motivated and ready to enter the workforce in particular became a fashion buyer who works in chain stores.